E.Coli Analysis of Settlement without Slums in Deli River Watershed, Hamdan Sub-District, Medan Maimun - Rahmadhani Fitri (Budapest International Research and Critics University, 2020)
The aim of the study is to find out E.Coli Analysis of Settlement without Slums in Deli River Watershed, Hamdan Sub-District, Medan Maimun. The results shows that E. Colli Laboratory amounting to 21420 - 36540/100 ml, still above the quality standards set by PP No.82 of 2001 concerning the management of water quality and control of water pollution. The results of the analysis of Total Coliform Laboratory of 198630 - 241960/100 ml, are still above the quality standards set by PP No.82 of 2001 concerning the management of water quality and control of water pollution. Alternative water treatment needs to be done before structuring buildings around the river location by means of filtration treatment and disinfecting. The arrangement that needs to be done next is to make a bathroom around the river location.